Automatic water level controlling and monitoring system using IoT application - muliadi, muliadi; Isminarti, Isminarti (Universitas Dharma Wacana, 2023)
Water tanks have recently been widely used in many applications in households or industry. It is essential to control the water level of a tank to regulate the filling process so that the tank does not overflow or empty without being noticed. This study aims to design an automatic water level control system using an IoT application to monitor and control processes. The sensor used in this study is a water level sensor, which detects the height of the water level. It works by the principle that the more water hitting the sensor, the smaller the resistance. The sensor can see whether the reservoir has reached a certain level or is complete. The sensor will inform the Wmos R1 board ESP8266 module to turn off the water pump engine and activate it again when the water level sensor reaches a certain level. The results show that the sensor worked correctly and accurately. When the water level sensor shows a whole height level in the filling process, which is 80% filled with water, the water level sensor will inform the Wmos R1 board ESP8266 module to change the relay to the OFF condition so that the water pump engine is also OFF. Upon detecting a specific height, when 50% of the tank has been filled with water, the pump engine restarts. The real-time ON/OFF status of the water pump monitoring the water using Telegram on a smartphone